2016
DOI: 10.1039/c5dt04961j
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel preparation of low oxygen content, high surface area silicon nitride and imidonitride materials

Abstract: Reactions of Si(NHMe)4 with ammonia are effectively catalysed by small ammonium triflate concentrations, and can be used to produce free-standing silicon imide gels. Firing at various temperatures produces amorphous or partially crystallised silicon imidonitride/nitride samples with high surface areas and low oxygen contents. The crystalline phase is entirely α-Si3N4 and structural similarities are observed between the amorphous and crystallised materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Ammonolytic gelation of Si(NHMe) 4 can be facilitated by the presence of a catalytic (∼0.4 mol%) amount of ammonium triflate, and the resulting gels can be fired to produce high quality silicon nitride/imido nitride materials with mesoporosity. 5 Ammonolysis of a 1 : 1 molar ratio of Si(NHMe) 4 and V(NMe 2 ) 4 under similar conditions did not result in gelation with or without the added triflate, instead a dark precipitate would separate from a turbid solution within a few hours of allowing the mixtures to warm to ambient temperature. Removal of solvent in vacuo from these mixtures resulted in colourless, low volatility, viscous liquid in the trap, which gelled on exposure to air and was probably the unreacted silicon amide and/or small oligomers.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Ammonolytic gelation of Si(NHMe) 4 can be facilitated by the presence of a catalytic (∼0.4 mol%) amount of ammonium triflate, and the resulting gels can be fired to produce high quality silicon nitride/imido nitride materials with mesoporosity. 5 Ammonolysis of a 1 : 1 molar ratio of Si(NHMe) 4 and V(NMe 2 ) 4 under similar conditions did not result in gelation with or without the added triflate, instead a dark precipitate would separate from a turbid solution within a few hours of allowing the mixtures to warm to ambient temperature. Removal of solvent in vacuo from these mixtures resulted in colourless, low volatility, viscous liquid in the trap, which gelled on exposure to air and was probably the unreacted silicon amide and/or small oligomers.…”
Section: Resultsmentioning
confidence: 95%
“…2 Silicon nitride is also of interest as a catalyst support due to the high thermal conductivity relative to the more commonly used silicas, and in the α-Si 3 N 4 form is oxidation resistant at typical catalytic process temperatures. 3,4 Gel-based routes to silicon nitrides and imidonitrides utilise solutionphase reactions of precursor molecules, usually amides, with cross-linking groups such as ammonia 5 or isocyanate. 6 These make polymeric species in solution, and when the polymeric material immobilises the liquid phase, the latter can be removed to provide high surface area materials that often contain basic surface groups.…”
Section: Introductionmentioning
confidence: 99%
“…It is still necessary to measure the quantity of ammonia, but the mixture can be assembled in a single reaction vessel and gelation occurs a period of time after the mixture warms to ambient temperature, with that period determined by the catalyst concentration [207]. This work showed that the triflate is incorporated and does result in some oxygen contamination, although this can be minimised by reducing its concentration to genuinely catalytic quantities (albeit with an increase in reaction time).…”
Section: Sol-gel Processing From Silicon Amides and Ammoniamentioning
confidence: 97%
“…During pyrolysis a number stages will occur and these may or may not involve an active gas environment such as NH3, and Si3N4 is placed in quotation marks above as this is only achieved at very high temperatures under ammonia. There is a clear possibility that carbon will also be incorporated from any alkyl groups present in the precursor, and imide groups persist even at 1400 °C in the amorphous material [207].…”
Section: Sol-gel Routes To Silicon Nitride and Related Materialsmentioning
confidence: 99%
See 1 more Smart Citation